Steroidal alkaloids efficient aromatase inhibitors with potential for the treatment of postmenopausal breast cancer. (10th November 2019) - Ali, Amjad; Jan, Naeem Ullah; Ali, Safdar; Ahmad, Bashir; Ali, Abid; Samrana, Samrana; Jahan, Azra; Ali, Hamid; Khan, Imtiaz Ali; Rahim, Haroon; Ali, Ijaz; Kifayatullah, Muhammad; et al.
Abstract: Plant‐derived natural products are of great interest due to their diversity in modern drug discovery. Sarcococca saligna has been used for the treatment of different diseases. The present study was aimed at isolating phytochemical constituents including Alkaloid‐C (a), Dictyophlebine (b), Sarcovagine‐D (c) and Saracodine (d) Holaphylline (e) from Sarcococca saligna to investigate the anticancer effect of these compounds. These compounds were evaluated for inhibition of aromatase enzyme of breast cancer in assistance by molecular docking simulations to understand molecular interaction between the enzyme and ligands. The IC50 values of compound 1 and 5 were found 138.27 ± 0.01 µl and 12.91 ± 0.01 µl, respectively, and both were found active due to their bulky structures in comparison to the active site of aromatase enzyme. The standard drug exemestane showed potent activity in comparison with the test compounds, having IC50 values of 0.052 ± 0.01 µl. Both compounds showed favorable electrostatic interactions with the active site of aromatase enzyme but the shape and steric bulk of the compounds was the limiting factor in their inhibitory effects. New lead compounds could be generated after extensive modifications guided by computational and experimental tools as a possible anticancer agents by targeting aromatase enzyme. Abstract : The steroidal alkaloids isolated from sarcococa saligna were explored as possible aromatase inhibitors in postmenopausal breast cancer by assistance of molecular simulation in order to understand molecular interactions of aromatase enzyme, standard drug exemestane, and ligands (holaphylline and alkaloid‐C). These compounds, holaphylline and alkaloid‐C, were found active against aromatase enzyme and showed favorable electrostatic interaction with active sites of aromatase enzyme.